2022
DOI: 10.1016/j.pubrev.2022.102156
|View full text |Cite
|
Sign up to set email alerts
|

How dialogic internal communication fosters employees’ safety behavior during the COVID-19 pandemic

Abstract: As employees return to the workplace amidst the COVID-19 pandemic, ensuring safety and health at work remains a top priority for organizations. Grounded in dialogic theory and protection motivation theory, this study examines how dialogic communication, as a type of strategic internal communication, can encourage employees to engage in safety behaviors in the workplace during the COVID-19 pandemic via heightened efficacy and perceived threat. An online survey of full-time employees of different industries retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 67 publications
1
16
0
2
Order By: Relevance
“…(Informant 4,Dircom,Commerce and Distribution) This model, based on dialogue and linkages, facilitates the transparent and smooth circulation of information, and makes the habits of sharing, coordinating, collaborating, engaging, integrating and involving all employees in the same business project viable. This view correlates with the most current literature research on IC (Berceruelo, 2020;Cuenca and Verazzi, 2020;Qin and Men, 2022;Ruck and Men, 2021;Tkalac, 2021;Theaker, 2022;Lee, 2022).…”
Section: The Role Of Internal Communication Before the Coronavirus Pa...supporting
confidence: 87%
“…(Informant 4,Dircom,Commerce and Distribution) This model, based on dialogue and linkages, facilitates the transparent and smooth circulation of information, and makes the habits of sharing, coordinating, collaborating, engaging, integrating and involving all employees in the same business project viable. This view correlates with the most current literature research on IC (Berceruelo, 2020;Cuenca and Verazzi, 2020;Qin and Men, 2022;Ruck and Men, 2021;Tkalac, 2021;Theaker, 2022;Lee, 2022).…”
Section: The Role Of Internal Communication Before the Coronavirus Pa...supporting
confidence: 87%
“…It was observed that after March 2022, the connections worsened (the approach was very difficult, including moments when the workers sustained that they didn’t understand their tasks. The effort made by the leadership to optimize the working media strengthens the bilateral engagement in the companies [ 52 ]. Staff and employee connection from corporations was much more difficult during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Para poder plantear los objetivos de investigación parece oportuno preguntarse si el conocimiento en el ámbito de las relaciones públicas previo a la crisis, así como el aportado por las más recientes investigaciones relacionadas con la crisis sanitaria provocada por la COVID (Abd-Alrazaq, 2020;Chen et al, 2020;Guo et al, 2021;Huang et al, 2022;Lee, 2022;Moreno et al, 2020;Xifra, 2020;Zeler et al, 2022), puede servir como marco de actuación para determinar el comportamiento de las organizaciones en una situación de crisis.…”
Section: Marco Teóricounclassified
“…La emergencia sanitaria causada por COVID-19, obligó a empresas y autoridades a establecer un diálogo con sus públicos para responder a las necesidades constantes de información (Bridman & Merkley, 2020;Huang et al, 2022). Ante estas circunstancias, la comunicación dialógica de las organizaciones con sus públicos se presenta como una herramienta estratégica para gestionar las crisis y construir relaciones de calidad (Lee, 2022). De hecho, las redes sociales se convirtieron en uno de los principales canales utilizados a la hora de trasladar las últimas noticias e indicaciones sanitarias a la población general (Bridman & Merkley, 2020) y complementaron el abanico de canales a través de los cuales los ciudadanos cubrieron sus necesidades de información (Moreno et al, 2021) En contextos diferentes a los de crisis, las redes sociales como Facebook, Twitter, TikTok o LinkedIn, también representan uno de los principales canales donde más se favorece el diálogo entre personas, organizaciones y sus stakeholders (Watkins, 2017;Yang & Saffer, 2019;Jiang & Park, 2021;Wang & Jang, 2019;Zhao & Chen, 2022).…”
unclassified